Integrating Gamification in a Blended Learning Entrepreneurship Course: Discussing Student Learning and Achievement Motivation - Seliro Wangi, Nisaul Barokati; Dewi, Yuli Ani Setyo; Munawaroh, Diah Ambarumi; Harsono; Zainuddin, Ammar; Mitra Zuana, Muhammad Mujtaba; Habsy, Bakhrudin All; Sirojuddin, Akhmad; Wandira, Septiana (International Journal of Psychosocial Rehabilitation, 2020)
Purpose Students’ passive activities, such as reading and watching activity make learning process can’t run well. Only active communication with their colleagues, facilitators, and other learning resources make process run well. In this case, we use gamification to improve student’s learning motivation. This study used four scales to obtain consistent and measurable data. Scale 1 and 2 were to analyze the level of knowledge about gamification framework, Scale 3 for concept and effectiveness and Scale 4 for fun learning. In conclusion, entrepreneurship courses through gamification run effectively because students are interested in gamification because it is new for them and able to establish good communication patterns as well as makes students more literate on technology...